Cloud Computing Adoption Using TOE Framework for Indonesia’s Micro Small Medium Enterprises - Gui, Anderes; Fernando, Yudi; Shaharudin, Muhammad Shabir; Mokhtar, Mazita; Karmawan, I Gusti Made; Suryanto, - (JOIV : International Journal on Informatics Visualization, 2020)
Cloud computing is one of the pillars of the Industrial Revolution 4.0. Cloud computing provides ample benefits to companies such as mobility, ease of access, and enable collaboration. Nevertheless, the impact of cloud computing on the micro, small and medium enterprises (MSMEs) is not well established. This research aims to classify the factors affecting the acceptance of cloud computing in Indonesian MSMEs. A total of 135 participants participated in this analysis. The TOE Structure is used in this analysis. Methods of data collection using Google form. The details have been analysed with SPSS and SmartPLS. The findings demonstrated that top management encouragement and relative advantages have a positive impact on the adoption of cloud computing in MSMEs in Indonesia. In order to increase the adoption of cloud-based computing in Indonesia, cloud-based businesses need to concentrate on these two reasons so that MSMEs in Indonesia can embrace more cloud computing. Furthermore, the improvement of cloud computing adoption should come from government policy and incentives. Theoretically, this research helps to establish the TOE framework by providing empirical evidence. This research also explains that the TOE framework can help companies to understand critical domains that impact their businesses and which domain companies should focus.